Ergonomic Criteria for Operating Room Design - Cortés-Sáenz, D.; Carrizosa-Morales, D. J.; Balderrama-Armendáriz, C. O.; De la Torre-Ramos, A. A.; Aguirre-Escárcega, F. E. (Revista Mexicana de Ingenieria Biomedica, 2020)
Personnel involved in the surgical area are affected with musculoskeletal injuries due to accumulated repetitive stress and movements. The severity of the injuries is given according to the work postures, the surgical specialty and the arrangement of the elements in the operating room. Ergonomics has become relevant since it has made very important contributions to working conditions in different areas. Although in the literature investigations of the frequency and effects of occupational injuries on surgical staff can be found, few studies have proposed guidelines for the ergonomic design of operating rooms. The present study encompasses four ergonomic criteria that should be considered for the design of operating rooms.